2011
DOI: 10.1038/mt.2010.250
|View full text |Cite
|
Sign up to set email alerts
|

The Complex and Evolving Story of T cell Activation to AAV Vector-encoded Transgene Products

Abstract: Original reports of adeno-associated virus (AAV) vector-mediated gene transfer to the muscle resulted in high-level β-galactosidase (β-gal) expression and the promise of a viral vector that was largely nonimmunogenic. Subsequent attempts to utilize these vectors for genetic vaccination, however, demonstrated that it was possible to activate cellular and humoral immunity to AAV-encoded antigens. These findings fueled years of investigation into factors impacting the immunogenicity of recombinant AAV-mediated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 94 publications
1
114
0
Order By: Relevance
“…Indeed, AAV-mediated gene transfers proved to be successful and resulted in sustained expression of therapeutic genes in a number of murine, canine, and simian tissues (1,10,23,27,30). Initial studies on the immune responses elicited by AAV-based vectors have focused on transgene product-specific immune responses and have indicated that although AAV is considered a poor activator of both innate and adaptive immunity (49), this feature highly depends on the transgene itself, the target tissue, the choice of promoter, and most importantly the host species (29). Viral capsids were also shown to be a source of antigens that activate T cell priming (45,47).…”
mentioning
confidence: 99%
“…Indeed, AAV-mediated gene transfers proved to be successful and resulted in sustained expression of therapeutic genes in a number of murine, canine, and simian tissues (1,10,23,27,30). Initial studies on the immune responses elicited by AAV-based vectors have focused on transgene product-specific immune responses and have indicated that although AAV is considered a poor activator of both innate and adaptive immunity (49), this feature highly depends on the transgene itself, the target tissue, the choice of promoter, and most importantly the host species (29). Viral capsids were also shown to be a source of antigens that activate T cell priming (45,47).…”
mentioning
confidence: 99%
“…Although the aforementioned generalized drug regimens can and have been used in conjunction with gene therapy, strategies to generate more ''immune-compatible'' vectors or specific immune tolerance protocols are also being assessed (Arruda et al, 2009;Nayak and Herzog, 2010;Mays and Wilson, 2011;Mingozzi and High, 2011). Strategies such as limiting expression to target tissues and avoiding expression in undesirable nontarget cells such as antigen-presenting cells by use of tissue-specific promoters have been shown to avoid provocation of a strong immune response.…”
Section: Complications Of Gene Therapy For Lsdsmentioning
confidence: 99%
“…Subsequent lack of major histocompatability complex I-mediated direct transgene presentation may allow rAAVs to evade the generation of a cytotoxic T-cell response; a mechanism likely contributing to rAAV-mediated long-term transgene expression. 7,8 Importantly, the use of ubiquitously active promoters, which can result in high off-target transgene expression in tissues other than the targeted organ, has been reported to drive transgene expression in antigen-presenting cells enabling major histocompatability complex I-mediated direct transgene presentation and development of transgenespecific immunity over time. 9 In addition, combined use of an rAAV serotype that readily transduces tissues other than the targeted organ can enhance the risk of triggering cellular immunity.…”
Section: Pleger Et Al Cardiac Calcium Handling On Trialmentioning
confidence: 99%
“…From this, we have learned that immune responses after rAAV gene delivery occur more readily in larger animal models and in humans. 7 Potential immune responses are transgene specific and influenced by ways of administration, choice of rAAV serotypes, as well as dosage, transgene expression levels, and expression control elements. Hence, long-term safety of rAAV1-cytomegalovirus-SERCA2a in humans cannot be taken for granted, particularly, because initial attempts at viral vector-based human gene therapy using retro-or adenoviruses in other fields have been met with issues of toxicity, either through activation of immunity or genomic integration and tumor formation.…”
Section: Pleger Et Al Cardiac Calcium Handling On Trialmentioning
confidence: 99%